Students’ Performance Comparison in Senior School Certificate Examination Arabic and Islamic Studies in Kwara State Nigeria - Abdullahi, Musa Siddiq (Departemen Pendidikan Bahasa Arab, 2021)
Arabic and Islamic education are inseparable as the knowledge of Arabic Language significantly complements that of Islamic Studies. The population of this study comprised all the senior secondary students offering Arabic and Islamic studies in Kwara State. To get the respondents, we used purposive sampling techniques with a population of students who sit in public and private high schools and have a record of studying Arabic and Islamic studies at WAEC and NECO SSCE. Research questions were answered with the percentage, mean and standard deviation, while the hypotheses were tested with the Person’s Chi- square at 0.05 alpha level, and the symmetric measure of Crammer’s V was used to determine the degree of relationship between the variables. Findings revealed that majority of students performed at the credit level (A1 to C6) in Arabic and Islamic Studies, Also, a significant correlation occurred between students’ performance in Arabic and Islamic Studies SSCE.